THE EFFECT OF INFLATION, BANK INDONESIA INTEREST RATE, AND EXCHANGE RATE ON STOCK RETURNS(A Study on Banking Companies Listed on the Indonesia Stock Exchange in 2021–2023) - I Made Paramartha Pandita; Ni Putu Santi Suryantini (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of macroeconomic variables namely inflation, the Bank Indonesia interest rate, and the exchange rate on the stock returns of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The background of this research is rooted in the importance of understanding how macroeconomic conditions can influence the financial sector, particularly the banking industry, which plays a strategic role in supporting the national economy. A quantitative approach was employed, utilizing multiple linear regression analysis. The study used secondary data obtained from annual financial reports of the companies and macroeconomic data from official sources such as Bank Indonesia and the IDX. The sample was selected using purposive sampling based on specific criteria, resulting in 12 banking companies as research subjects. The findings indicate that inflation has a negative but insignificant effect on stock returns. The Bank Indonesia interest rate shows a positive yet insignificant effect on stock returns. Meanwhile, the rupiah exchange rate against the US dollar exhibits a negative and insignificant effect on banking stock returns. These results suggest that the examined macroeconomic variables do not have a significant effect on stock returns in the banking sector during the observation period. Therefore, investors are advised to consider other factors, such as the company's fundamental performance and microeconomic dynamics, when making investment decisions.